A new species of Batillipes (Arthrotardigrada: Batillipedidae) from the mid littoral zone of the southeast coast of India - Vishnudattan, N. K.; Rubal, Marcos; Nandan, S. Bijoy (Zootaxa, 2023)
Studies of marine tardigrades from Indian waters is very limited and relatively obscure. A new species of marine tardigrade is described from the southeast coast of India as part of an effort to better understand the marine tardigrade biodiversity of the Indian subcontinent. Batillipes kalami sp. nov. described from the sandy sediments of the mid littoral zone can be differentiated from all its congeners by the presence of unconstricted primary clavae, two pairs of lateral body projections between leg II and leg III, long and blunt ended lateral body projections between leg III and leg IV, shape of leg IV sensory organs and the presence of dorsal indentations in its head.